Drosophila Nesprin-1 Isoforms Differentially Contribute to Muscle Function - Alexandre Rey (MDPI AG, 2021)
Nesprin-1 is a large scaffold protein connecting nuclei to the actin cytoskeleton via its KASH and Calponin Homology domains, respectively. Nesprin-1 disconnection from nuclei results in altered muscle function and myonuclei mispositioning. Furthermore, Nesprin-1 mutations are associated with muscular pathologies such as Emery Dreifuss muscular dystrophy and arthrogryposis. Nesprin-1 was thus proposed to mainly contribute to muscle function by controlling nuclei position. However, Nesprin-1′s localisation at sarcomere’s Z-discs, its involvement in organelles’ subcellular localization, as well as the description of numerous isoforms presenting different combinations of Calponin Homology (CH) and KASH domains, suggest that the contribution of Nesprin-1 to muscle functions is more complex. Here, we investigate the roles of Nesprin-1/Msp300 isoforms in muscle function and subcellular organisation using Drosophila larvae as a model. Subsets of Msp300 isoform were down-regulated by muscle-specific RNAi expression and muscle global function and morphology were assessed. We show that nuclei anchoring in mature muscle and global muscle function are disconnected functions associated with different Msp300 isoforms. Our work further uncovers a new and unsuspected role of Msp300 in myofibril registration and nuclei peripheral displacement supported by Msp300 CH containing isoforms, a function performed by Desmin in mammals.